PENGARUH KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi pada PT. Bank Rakyat Indonesia Kantor Cabang Sumedang) - Anisa Mumtazah Dhiya Ulhaq; Ahmad Abdul Gani (Laboratorium FEBI UIN SGD Bandung, 2024)
Companies need employees who can provide extra roles that can have a good impact on the company. The extra role is known as organizational citizenship behavior (OCB). Organizational citizenship behavior is an optional behavior outside of the employee's job desk, but can have a positive impact on the company. There are several factors that can affect OCB from internal factors, one of which is job satisfaction, while one of the external factors is organizational culture. This study aims to determine whether there is an effect of job satisfaction and organizational culture on organizational citizenship behavior at PT. Bank Rakyat Indonesia (Persero) Tbk. Sumedang Branch Office. The method used in this research is descriptive verification method through a quantitative approach. Data analysis techniques used include descriptive analysis, validity and reliability tests, multiple linear regression analysis, t test, F test, and test the coefficient of determination. The results of the study state that job satisfaction and organizational culture have a significant effect on organizational citizenship behavior. Keywords: Job Satisfaction, Organizational Culture, Organizational Citizenship Behavior